ANALISIS PENDAPATAN USAHA TERNAK KAMBING PERANAKAN ETAWA DAN JAWARANDU DI KELOMPOK TANI MAKMUR DESA PAYAK KECAMATAN CLUWAK KABUPATEN PATI - Munif Murdiandi; Dewi Hastuti; Rossi Prabowo; Endah Subekti (MEDIAGRO, 2020)
The analysis of business income of Cross Breed Etawa and Jawarandu goats out to evaluate and help farmers to conduct sustainable businees well. The purpose of this study was to determine the management of fattening, total cost, revenue, know the business income of the Cross Etawa and Jawarandu goats and determine the level of R/C in the Cross Etawa and Jawarandu goat business. The method of sampling respondents using the census method and analytical method used is the feasibility analysis method of farming. The results showed that the management of fattening 4 months in 1 period, with a 4-6 month age, there are 2 types of feed given, namely forage and concentrate by giving twice a day, with a cage size of ± 1m2 / head. For the total business cost of Cross Etawa goats amounting to Rp.134,642,290, revenue of Rp.157,500,000, and income of Rp.22,907,710 while Jawarandu goat business total costs of Rp.118,860,455, revenue of Rp.126,650,000, and income of Rp.7,969 .555. The R/C value of Cross Etawa goat business is 1.165 while the R/C value of Jawarandu goats is 1.07. It can be concluded that business are feasible, b the cross breed Etawa goat provides greater revenue and income than the Jawarandu goat. Keywords : Analysis Income, Goat, R/C